English Vocabulary Learning Strategies Used by Undergraduate Science Education Students - Supriadi; yusrah (English Lecturers and Teachers Association (ELTA), 2025)
This study aims to explore the English vocabulary learning strategies used by undergraduate science education students and the challenges they face. A total of 53 students from various science education programs participated in the study. Using a descriptive quantitative and qualitative approach, data were collected through a questionnaire by Likert-scale items and open-ended questions. The quantitative data were analyzed using descriptive statistics, while the qualitative responses were examined through content analysis to identify recurring themes. The results showed that students most frequently used digital tools, particularly using Google Scholar, Wikipedia, or search engines to find word meanings and usage (mean score = 3.53; 70.6%), followed by rewriting new words (3.21; 64.2%) and verbal repetition (3.09; 61.8%). However, 41.5% of students reported that they rarely read scientific texts in English, and 22.6% said they very rarely do so. Common challenges identified included the complexity and unfamiliarity of scientific terms, difficulty in memorization, low motivation, and limited opportunities for practice and exposure. It is recommended that science education programs provide more structured exposure to English texts, apply contextual vocabulary teaching, and encourage the use of digital tools and collaborative learning. Keywords : English. Vocabulary, Science